Long-term tolerance of islet allografts in nonhuman primates induced by apoptotic donor leukocytes - Amar Singh (Nature Portfolio, 2019)
Injection of donor apoptotic cells induces graft tolerance in mice. Here the authors combine this approach with short immunosuppressive therapy to achieve long-term tolerance to allogeneic islets and restoration of normoglycemia in diabetic nonhuman primates, and delineate cellular and molecular correlates of tolerance induction.